Faktor Pendukung dan Penghambat Implementasi Hak ANDIKPAS di LPKA Kelas II Pekanbaru - Sri Yunita Simanjuntak; Elfira Elfira; Nurfadilah Nurfadilah (Majalah Ilmiah METHODA, 2026)
This study is entitled: Supporting and Inhibiting Factors in the Implementation of ANDIKPAS Rights in the Class II Pekanbaru LPKA. This study was conducted at the Class II Pekanbaru Special Child Development Institution. The purpose of this study is to analyze the supporting and inhibiting factors in the implementation of ANDIKPAS rights in the Class II Pekanbaru LPKA. The results of the study show that the supporting and inhibiting factors for the implementation of students' rights are seen from the actors involved in the implementation, namely all LPKA Class II Pekanbaru employees and do not involve actors from outside the agency, this simplifies the chain of command in implementing the policy, in terms of clarity of objectives it has been fully understood by the implementer, but is not implemented as written in the SOP because the human resources in LPKA are inadequate, then from the development and complexity of the policy, the success of the policy implementation cannot be separated from the role of parents who support the policy and the acceptance of parents so that in the future children do not feel isolated, then the participation given by stakeholders, namely the Riau Ministry of Law and Human Rights in building facilities and infrastructure and the Library and Archives Service in providing mobile libraries plays an important role in granting students' rights, and other factors are inadequate facilities and infrastructure, such as the availability of library buildings for ANDIKPAS that need to be provided and the lack of freedom for ANDIKPAS in submitting complaints directly to the KALAPAS.